Electrolyte and lithium metal battery
By using some fluorocarbonate, fluoroether and dioxadipate in the electrolyte of lithium metal batteries, a stable interface film is formed, which solves the problems of oxidative decomposition of electrolyte and side reactions of lithium metal under high voltage, and achieves stable cycle and long life of the battery.
Patent Information
- Application Number
- CN202510042354.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
At high voltage, the electrolyte of lithium metal batteries has severe oxidation and decomposition on the positive electrode surface and the lithium metal surface reaction are severe, resulting in a short battery cycle life.
A partial fluorocarbonate solvent system is used to introduce fluoroether and dioxadipate to regulate the addition of lithium nitrate, form a stable interface film, and reduce the high-pressure decomposition of the electrolyte and the side reaction of lithium metal surface.
The oxidation resistance of the electrolyte is improved, the reactivity of the electrolyte on lithium metal is reduced, and a stable SEI film is formed, which extends the cycle life of the lithium metal battery and achieves stable cycle at a high voltage of 4.7V.
Smart Images

Figure BDA0005237328560000061 
Figure BDA0005237328560000071 
Figure BDA0005237328560000072
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-voltage lithium metal batteries, and in particular to an electrolyte and a lithium metal battery. Background Art
[0002] Lithium batteries have become the preferred choice for many battery applications due to their high energy density and long life. For example, electric vehicles, digital products, energy storage devices, drones, etc. Higher energy density, longer service life, faster charging speed and better safety have always been the goals pursued by the industry. Ultra-high energy density (>500Wh / kg) batteries require high operating voltage and high capacity, which places high demands on the electrolyte. The electrolyte not only faces the problem of gas production and consumption due to oxidation decomposition under high voltage of the positive electrode, but also faces a series of problems such as unstable film formation and serious side reactions caused by high-capacity negative electrodes such as silicon-based materials and lithium metal due to high reactivity and material expansion.
[0003] Patent CN114824481A utilizes the synergistic effect of boron-containing lithium salts, methylsilyl (sub)phosphate compounds and hydrofluoroether solvents in the electrolyte to improve the electrochemical window of the electrolyte, and form a uniform and dense CEI film on the surface of the positive electrode, thereby improving the cycle stability of the battery; although this patent uses hydrofluoroether solvents, boron-containing lithium salts and methylsilyl (sub)phosphate compounds in the electrolyte to form a uniform and dense CEI film on the surface of the positive electrode, thereby improving the electrochemical window and enhancing the cycle stability of the battery, the electrolyte modification of this patent only targets the problems faced by the positive electrode, and does not have a targeted improvement strategy for the problems of high reaction activity of metallic lithium, many side reactions, and lithium dendrite growth on the negative electrode side.
[0004] Patent CN115395097A uses indium nitrate or indium chloride as the first additive, lithium difluorooxalate borate as the second additive, and lithium nitrate dissolved in a sulfone solvent or an ether solvent as the third additive, and simultaneously introduces the three additives into an ether electrolyte for synergistic modification, so that the electrolyte can spontaneously react on the surface of the metal lithium negative electrode to generate a solid electrolyte interface film with a hierarchical structure, which has the characteristics of ideal high ion diffusion capacity, high resistivity and high Young's modulus, thereby improving the cycle stability of the metal lithium negative electrode; although this patent generates a solid electrolyte interface film with a hierarchical structure on the surface of the metal lithium negative electrode by adding multiple additives such as indium nitrate or indium chloride, lithium difluorooxalate borate and lithium nitrate to the electrolyte, and using an ether electrolyte, thereby improving the cycle stability of the metal lithium negative electrode, the electrolyte in this patent uses an ether solvent and has poor high voltage resistance. The patent also does not make targeted optimizations for a series of problems faced by batteries under high voltage, such as oxidation and decomposition of the electrolyte on the positive electrode surface. Summary of the invention
[0005] In view of the problems faced by conventional electrolytes in high-voltage lithium metal battery applications, such as oxidation and decomposition of the electrolyte on the positive electrode surface and severe side reactions on the lithium metal surface, resulting in the growth of lithium dendrites, which lead to short battery cycle life, the present invention provides an electrolyte and a lithium metal battery.
[0006] In the present application, a partially fluorinated carbonate solvent system is used to improve the intrinsic oxidation resistance of the electrolyte, a fluorinated ether solvent is introduced to reduce the reactivity of the electrolyte to lithium metal, a new solvent dioxaadipic acid ester is introduced and the dosage is regulated, and a stable interface film is formed on the positive and negative electrode surfaces, reducing the high-voltage decomposition of the electrolyte and the side reactions on the lithium metal surface, inhibiting the growth of lithium dendrites, and maintaining a high conductivity, and regulating the amount of lithium nitrate added to form a stable SEI film while reducing the battery impedance, thereby achieving a stable cycle of lithium metal batteries at high voltages
[0007] In a first aspect, the present application provides an electrolyte:
[0008] An electrolyte, comprising a lithium salt, a solvent and an additive; the concentration of the lithium salt in the solvent is 0.8-1.2 mol / L; the mass fraction of the additive in the electrolyte is 1-2 wt%;
[0009] The additive includes lithium difluorophosphate (LiDFP) and lithium nitrate (LiNO3) and contains any one or more of indium trifluoromethanesulfonate (In(Otf)3) and dimethyl sulfoxide (DMSO);
[0010] The solvent includes any one or more combinations of cyclic carbonates, linear carbonates, fluorinated cyclic carbonates, fluorinated linear carbonates, fluorinated ethers and dioxaadipic acid esters.
[0011] Furthermore, the additive is a composition of 1% by mass of lithium difluorophosphate, 0.01-0.2% of lithium nitrate and 0.01-0.2% of indium trifluoromethanesulfonate based on the total mass fraction of the electrolyte.
[0012] Furthermore, the additive is a composition of 1% by mass of lithium difluorophosphate, 0.07-0.15% of lithium nitrate and 0.01-0.2% of indium trifluoromethanesulfonate based on the total mass fraction of the electrolyte.
[0013] Furthermore, the mass fraction of the dioxaadipic acid ester in the solvent is 1-10%.
[0014] Furthermore, the mass fraction of the dioxaadipic acid ester in the solvent is 2-8%.
[0015] Furthermore, the solvent includes fluorinated cyclic carbonates, fluorinated linear carbonates and fluorinated ethers.
[0016] Furthermore, the total amount of fluorinated cyclic carbonate, fluorinated linear carbonate and fluorinated ether in the solvent accounts for 55-70% of the mass of the solvent.
[0017] Further, the lithium salt includes any one or more combinations of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium perchlorate and lithium hexafluoroarsenate;
[0018] Further, the cyclic carbonate includes any one or more combinations of ethylene carbonate (EC) and propylene carbonate (PC);
[0019] The linear carbonate is at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC);
[0020] The fluorinated cyclic carbonate includes any one or more combinations of fluoroethylene carbonate (FEC) and trifluoropropylene carbonate (TFPC);
[0021] The fluorinated linear carbonate includes any one or more combinations of trifluoroethyl methyl carbonate (FEMC) and bis(2,2,2-trifluoroethyl) carbonate (DFDEC);
[0022] The fluoroether includes any one or more combinations of 2,2,2-trifluoroethyl ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE);
[0023] The dioxaadipate ester includes any one or more combinations of dimethyl 2,5-dioxaadipate (DMDOHD) and diethyl 2,5-dioxaadipate (DEDOHD).
[0024] The present application provides an electrolyte: in order to address the problem of oxidative decomposition of the electrolyte on the positive electrode surface under high voltage, the electrolyte of the present application can improve the intrinsic oxidation resistance of the electrolyte by partially replacing the carbonate in the solvent with a fluorocarbonate, while controlling the solvent viscosity to increase moderately and the solubility of the lithium salt to decrease moderately, thereby making the electrolyte conductivity and lithium salt concentration within a normal range.
[0025] Traditional battery electrolytes generally use cyclic carbonates (such as ethylene carbonate (EC) and propylene carbonate (PC)) and chain carbonates (such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC)) as the main solvents. However, ordinary carbonate solvents have poor high-voltage resistance, and the upper limit voltage is generally below 4.5V. When the voltage is too high, the electrolyte will be severely oxidized and decomposed. By partially replacing the carbonate in the solvent with fluorocarbonate, the intrinsic oxidation resistance of the electrolyte can be improved, while controlling the solvent viscosity to increase moderately and the solubility of lithium salt to decrease moderately, so that the electrolyte conductivity and lithium salt concentration are within the normal range.
[0026] In view of the problem that carbonate solvents still face high reaction activity with lithium metal in the application of lithium metal batteries, further, fluoroether and fluorocarbonate are added to the solvent of the present application, which improves the intrinsic oxidation resistance of the solvent, while also reducing the reaction activity of the electrolyte to lithium metal, forming a uniform and stable SEI film, and reducing the occurrence of side reactions on the surface of lithium metal.
[0027] Furthermore, the introduction of a new solvent dioxaadipate into the electrolyte can form a uniform and stable CEI film on the positive electrode surface, protect the positive electrode, and reduce the high-voltage decomposition of the electrolyte. Dioxaadipate can also form a protective SEI film on the surface of the metal lithium negative electrode to reduce the occurrence of side reactions on the lithium metal surface; however, due to the high viscosity of dioxaadipate, an appropriate amount of dioxaadipate is used to ensure appropriate conductivity, and at the same time, an appropriate amount of lithium nitrate is used to form a firm and stable SEI film on the lithium metal surface without causing other side reactions, thereby improving the battery cycle life.
[0028] The present invention adopts carbonate, fluorocarbon and fluoroether as basic solvents, and realizes the stable cycle of high-voltage lithium metal battery by regulating the dosage of lithium nitrate and dioxaadipate.
[0029] In a second aspect, the present application provides a lithium metal battery:
[0030] A lithium metal battery comprises a positive electrode, a negative electrode, a separator and an electrolyte.
[0031] Furthermore, the positive electrode active material is one of lithium-manganese-rich and lithium nickel manganese oxide high-voltage positive electrode materials.
[0032] Furthermore, the lithium metal soft-pack battery has a cycle life of over 50 cycles at a high voltage of 4.7V.
[0033] In view of the problem that lithium metal has high reactivity and is prone to lithium dendrite growth in lithium metal batteries, which leads to short battery cycle life; the present application provides a lithium metal battery with a long battery cycle life. Carbonate, fluorocarbonate and fluoroether are used as basic solvents in the electrolyte of the lithium metal battery, and fluoroether and dioxaadipate are used to reduce the side reaction on the surface of lithium metal, and an appropriate amount of lithium nitrate is added, so that the electrolyte can not only adapt to the high-voltage positive electrode and the lithium metal negative electrode at the same time, but also form a stable SEI film while reducing the battery impedance, and can also maintain a high conductivity and lithium salt concentration, so as to achieve stable circulation of lithium metal batteries at high voltage.
[0034] Beneficial effects:
[0035] 1. The electrolyte of the present invention adopts carbonate, fluorinated carbonate and fluorinated ether as basic solvents. By adjusting the amount of lithium nitrate and dioxaadipic acid ester, the intrinsic oxidation resistance of the electrolyte is improved, and the reaction activity of the electrolyte to lithium metal is reduced. At the same time, a stable protective interface film is formed on the surface of the positive and negative electrodes, which reduces the side reactions of the electrolyte on the surface of the positive and negative electrodes, reduces the decomposition of the electrolyte, inhibits the growth of lithium dendrites, reduces the battery impedance, and realizes that the lithium metal soft-pack battery has a cycle life of more than 50 cycles at a high voltage of 4.7V.
[0036] 2. The types and weights of additives in the electrolyte were further optimized, which further improved the oxidation resistance of lithium metal batteries, reduced battery impedance and stabilized cycle performance under high voltage.
[0037] 3. The amounts of lithium difluorophosphate, lithium nitrate, indium trifluoromethanesulfonate and dioxaadipic acid ester in the electrolyte were further optimized, which further improved the oxidation resistance of lithium metal batteries, reduced battery impedance and achieved stable cycle performance at high voltage. DETAILED DESCRIPTION
[0038] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0039] Example 1
[0040] Embodiment 1, a lithium metal battery:
[0041] Raw materials used in electrolyte:
[0042] Solvent: Based on the total mass of the solvent, it includes 15% by mass of fluoroethylene carbonate FEC (fluorinated cyclic carbonate), 40% by mass of ethyl methyl carbonate EMC (linear carbonate), 35% by mass of FEMC (fluorinated linear carbonate) and 10% by mass of TTE (fluoroether).
[0043] Lithium salt: lithium hexafluorophosphate, the concentration in the solvent is 1.0 mol / L.
[0044] Additive: LiDFP (lithium difluorophosphate) with a mass fraction of 1% based on the total amount of electrolyte.
[0045] Preparation of electrolyte:
[0046] The moisture content in the glove box is controlled to be less than 10ppm, and the moisture content in the solvent is controlled to be less than 10ppm. Use a pipette to accurately transfer different solvents in the glove box according to a certain ratio, transfer them to an aluminum bottle, stir them thoroughly and store them in a constant temperature box at 0℃ for 1h. Then, lithium hexafluorophosphate and 1% LiDFP by mass are added to the mixed solvent at a concentration of 1.0mol / L, stirring while adding to prepare an electrolyte for standby use.
[0047] Preparation of lithium metal batteries:
[0048] The lithium metal battery includes a positive electrode, a negative electrode, a separator and the above-mentioned electrolyte.
[0049] The positive electrode active material (using lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2), conductive agent, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 93:2.5:2:2.5, dispersed in N-methylpyrrolidone, and then fully stirred according to the homogenization process to obtain a positive electrode slurry with a solid content of 70%. The evenly dispersed positive electrode slurry was evenly coated on an aluminum foil with a thickness of 12μm, and a positive electrode sheet was obtained after baking, rolling, slitting, and punching, wherein the positive electrode slurry coating thickness was 65μm.
[0050] Negative electrode: The active material of the negative electrode is metallic lithium. The lithium-copper composite foil (lithium layer thickness 20 μm, copper layer thickness 8 μm) is baked, rolled, slit, and punched to obtain the negative electrode sheet.
[0051] Diaphragm: PE diaphragm.
[0052] After the positive and negative electrodes are punched, the positive electrode is placed in an oven at 130°C, and the negative electrode is placed in an oven at 100°C for 25 hours. When the moisture content of the electrode sheet meets the requirements, the positive electrode sheet, the negative electrode sheet and the diaphragm are placed in a stacking machine to stack into bare cells, and the bare cells are packaged in stamped aluminum-plastic film bags. After the packaged dry cells are dried at 90°C for 11 hours, the electrolyte of the present invention is injected into the dry cells, and the cells are placed, formed, placed at high temperature, evacuated and sealed, and divided into different volumes to obtain lithium metal batteries.
[0053] Example 2, a lithium metal battery, differs from Example 1 in that the additives used are 1% LiDFP (lithium difluorophosphate), 0.01% LiNO3 and 0.01% In(Otf)3 (indium trifluoromethanesulfonate) in a mass fraction of the total amount of the electrolyte.
[0054] Example 3, a lithium metal battery, differs from Example 1 in that the additives used are 1% by mass of LiDFP (lithium difluorophosphate), 0.05% of LiNO3 and 0.05% of In(Otf)3 in the total amount of the electrolyte.
[0055] Example 4, a lithium metal battery, differs from Example 1 in that the additives used are 1% LiDFP (lithium difluorophosphate), 0.1% LiNO3 and 0.1% In(Otf)3 in a mass fraction of the total amount of the electrolyte.
[0056] Example 5, a lithium metal battery, differs from Example 1 in that the additives used are 1% LiDFP (lithium difluorophosphate), 0.2% LiNO3 and 0.2% In(Otf)3 in mass fraction of the total amount of the electrolyte.
[0057] Example 6, a lithium metal battery, is different from Example 4 in that 1% by mass of ethyl methyl carbonate EMC (linear carbonates) in the solvent is replaced by an equal amount of dimethyl 2,5-dioxadipic acid DMDOHD (fluoroethers).
[0058] Example 7, a lithium metal battery, is different from Example 4 in that 5% by mass of EMC in the solvent is replaced by an equal amount of DMDOHD.
[0059] Example 8, a lithium metal battery, is different from Example 4 in that 10% by mass of EMC in the solvent is replaced by an equal amount of DMDOHD.
[0060] Comparative Example 1 is a lithium metal battery, which is different from Example 1 in that an equal amount of the solvent is replaced with a composition of ethylene carbonate EC (cyclic carbonate) and EMC in a mass ratio of 15:85.
[0061] Comparative Example 2, a lithium metal battery, differs from Example 1 in that an equal amount of the solvent is replaced with a composition of FEC (fluorinated cyclic carbonate), EMC and FEMC (fluorinated linear carbonate) in a mass ratio of 15:45:40.
[0062] Performance Test:
[0063] (1) Electrolyte conductivity test
[0064] The electrolytes used in Examples 1-8 and Comparative Examples 1-2 were tested for room temperature conductivity using a conductivity tester. Specific test data are shown in Table 1.
[0065] (2) Lithium metal battery room temperature formation test
[0066] The lithium metal batteries of Examples 1-8 and Comparative Examples 1-2 were subjected to room temperature formation tests according to the following steps. The detailed steps are as follows: Take a fresh lithium metal battery and set it aside for more than 10 hours. Then charge it at 0.1C room temperature constant current and constant voltage, with a cut-off voltage of 4.7V and a cut-off current of 0.05C to obtain the first charging capacity. Then discharge it at 0.1C room temperature constant current to 2.0V to obtain the first discharge capacity. Then charge it at 0.1C constant current with a cut-off voltage of 4.7V, then discharge it at 0.1C constant current to 30% SOC, let it stand for one hour, and perform a 20-second discharge test on the battery cell with a 0.25C pulse current. According to the change in voltage, calculate the capacity distribution DCR of the battery. See Table 2 for specific test data.
[0067] (3) Lithium metal battery room temperature cycle test
[0068] The lithium metal batteries of Examples 1-8 and Comparative Examples 1-2 were subjected to a room temperature cycle test according to the following steps. The detailed steps are as follows: Take the lithium metal battery after constant capacity and set it aside for more than 1 hour. Then, at room temperature, charge it at a constant current of 0.1C, with a cut-off voltage of 4.7V, and then discharge it at a constant current of 0.1C to 2.0V. According to the above steps, the battery was charged and discharged in cycles, and the discharge capacity of the first cycle, the discharge capacity after 50 cycles, and the capacity retention rate were recorded. Specific test data are shown in Table 3.
[0069] Table 1. Conductivity of the electrolyte used in Examples 1-8 and Comparative Examples 1-2
[0070]
[0071]
[0072] Table 2. List of room temperature formation tests of lithium metal batteries of Examples 1-8 and Comparative Examples 1-2
[0073]
[0074] Table 3. List of normal temperature cycle tests of lithium metal batteries of Examples 1-8 and Comparative Examples 1-2
[0075]
[0076] Comparative Example 1 uses only traditional non-fluorinated carbonate solvents EC and EMC, which have poor oxidation resistance. Under high pressure, the solvent is prone to oxidative decomposition, resulting in too high first charge capacity during formation, low first discharge capacity, low first efficiency, large battery impedance, and low first discharge capacity during the cycle. The battery cannot complete 50 cycles. The high first efficiency can be explained by the addition of DMDOHD, which makes the positive electrode film better and reduces the high-pressure decomposition of the electrolyte; the low first efficiency indicates that the high-pressure decomposition of the electrolyte is more.
[0077] Compared with Comparative Example 1, in Comparative Example 2, the fluorinated cyclic carbonate FEC replaces EC, and the fluorinated linear carbonate FEMC partially replaces EMC. Although the high viscosity of FEMC reduces the conductivity of the electrolyte, the oxidation resistance of the solvent is improved, the first charge capacity during formation is reduced to a normal level, the first discharge capacity and the first efficiency are significantly improved, the decomposition of the electrolyte is reduced, the DCR is significantly reduced, the first discharge capacity of the cycle is significantly improved, and the capacity retention rate after 50 cycles is 51.8%.
[0078] Compared with Comparative Example 2, in Example 1, 10% by mass of fluoroether TTE was added to the solvent to replace 10% of the linear carbonate (including 5% EMC and 5% FEMC). Since TTE does not participate in the solvation structure, the conductivity is slightly reduced. Fluorinated ether has a low effect on the reactivity of lithium metal, the impedance of the SEI film formed during formation is low, the first effect is improved, the side reactions on the surface of lithium metal are reduced during the cycle, and the cycle capacity retention rate is improved.
[0079] Compared with Example 1, when less than 0.2% LiNO3 is added in Examples 2-5, the effect on the conductivity of the electrolyte is very small. When the amount of LiNO3 added increases from 0.01% to 0.1% (Examples 2-4), the battery impedance gradually decreases, the first efficiency gradually increases, and the cycle capacity retention rate also increases accordingly. The addition of lithium nitrate can form a firm and stable SEI film on the surface of lithium metal, inhibit the growth of lithium dendrites, reduce the formation of dead lithium, and improve the cycle life of the battery. In Example 5, when the amount of LiNO3 added is increased to 0.2%, the first charge capacity of the formation is high, the first efficiency is low, the DCR is high, and the cycle capacity retention rate is also reduced. At this time, the excess lithium nitrate may react with the lithium-rich manganese positive electrode, resulting in electrolyte decomposition, increased impedance, and reduced cycle performance.
[0080] In Example 6-8, 1%-10% of the new ester solvent DMDOHD is further added on the basis of Example 4. Due to the high viscosity of DMDOHD, the conductivity of the electrolyte decreases as the amount of DMDOHD added increases. Compared with Example 4, when the amount of DMDOHD added is less (Example 6, 1%), there is no significant improvement in the various performances of the battery; when the amount of DMDOHD added is increased to 5% (Example 7), the first charge capacity during formation is reduced, the first discharge capacity is increased, the first efficiency is improved, and when the conductivity decreases more, the DCR increases less, and the cycle capacity retention rate is significantly improved. DMDOHD can not only form a uniform and stable CEI film on the lithium-rich manganese positive electrode, protect the positive electrode, and reduce the high-voltage decomposition of the electrolyte, but also form a protective SEI film on the surface of the metal lithium negative electrode, reduce the occurrence of side reactions on the lithium metal surface, thereby reducing impedance and improving cycle life. However, when the amount of DMDOHD added is further increased (Example 8, 10%), the conductivity decreases more, the volumetric DCR is larger, the discharge capacity decreases, and the cycle capacity retention rate decreases significantly.
[0081] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An electrolyte, characterized in that: The invention comprises a lithium salt, a solvent and an additive; the concentration of the lithium salt in the solvent is 0.8-1.2 mol / L; the mass fraction of the additive in the electrolyte is 1-2 wt%; The additive includes any one or more combinations of lithium difluorophosphate, lithium nitrate, indium trifluoromethanesulfonate and dimethyl sulfoxide; The solvent includes any one or more combinations of cyclic carbonates, linear carbonates, fluorinated cyclic carbonates, fluorinated linear carbonates, fluorinated ethers and dioxaadipic acid esters.
2. The electrolyte according to claim 1, characterized in that The additive is a composition of 1% lithium difluorophosphate, 0.01-0.2% lithium nitrate and 0.01-0.2% indium trifluoromethanesulfonate in a mass fraction of the total amount of the electrolyte.
3. The electrolyte according to claim 2, characterized in that The additive is a composition of 1% lithium difluorophosphate, 0.07-0.15% lithium nitrate and 0.01-0.2% indium trifluoromethanesulfonate in a mass fraction of the total amount of the electrolyte.
4. The electrolyte according to claim 2, characterized in that The mass fraction of the dioxaadipic acid ester in the solvent is 1-10%.
5. The electrolyte according to claim 4, characterized in that The mass fraction of the dioxaadipic acid ester in the solvent is 2-8%.
6. The electrolyte according to claim 1, characterized in that The solvents include fluorinated cyclic carbonates, fluorinated linear carbonates and fluorinated ethers.
7. The electrolyte according to claim 6, characterized in that The total amount of the fluorinated cyclic carbonate, the fluorinated linear carbonate and the fluorinated ether in the solvent accounts for 55-70% of the mass of the solvent.
8. The electrolyte according to claim 1, characterized in that The lithium salt includes any one or more combinations of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium perchlorate and lithium hexafluoroarsenate.
9. The electrolyte according to claim 1, characterized in that The cyclic carbonate includes any one or more combinations of ethylene carbonate and propylene carbonate; The linear carbonate comprises any one or more combinations of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; The fluorinated cyclic carbonate includes any one or more combinations of fluoroethylene carbonate and trifluoropropylene carbonate; The fluorinated linear carbonate includes any one or more combinations of methyl trifluoroethyl carbonate and bis(2,2,2-trifluoroethyl) carbonate (DFDEC); The fluoroether includes any one or more combinations of 2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether; The dioxaadipic acid ester includes any one or more combinations of dimethyl 2,5-dioxaadipate and diethyl 2,5-dioxaadipate.
10. A lithium metal battery using the electrolyte according to any one of claims 1 to 9, characterized in that: It includes positive electrode, negative electrode, separator and electrolyte.